Reliability and availability evaluation on hydraulic system of ship controllable pitch propeller based on evidence theory and dynamic Bayesian network. (15th May 2023) - Bai, Xu; Ling, Hao; Luo, Xiao-fang; Li, Yu-shan; Yang, Li; Kang, Ji-chuan
Abstract: The hydraulic system is the main power source for the pitch adjustment of the ship's controllable pitch propeller. The stable operation of the system is the guarantee of ship navigation safety. Therefore, it is necessary to analyze the reliability and availability of the hydraulic system of the controllable pitch propeller. In order to deal with epistemic uncertainty and dynamic characteristics in the reliability and availability assessment process of controllable pitch propeller hydraulic systems，the D-S evidence theory and dynamic Bayesian network were applied to establish a novel approach for assessing its reliability and availability. The proposed approach included: (1) analyzing the working principle of the system to establish a reliability block diagram; (2) according to the reliability block diagram, the system dynamic fault tree is established and transformed into DS-DBN model; (3) parameter learning and structure learning of DS-DBN model of controlled pitch propeller hydraulic system; and (4) system reliability and availability calculation, analysis of epistemic importance and weak links. The applicability of the approach was verified by comparison of Markov calculations. Highlights: An approach framework based on DS-DBN model is proposed for ship system reliability and availability analysis. It can handle epistemic uncertainty and dynamic characteristics in ship system reliability and availability evaluation. The approach is used to evaluate the reliability and availability of ship controllable propeller hydraulic system.